Quality in WIPO Domain Name Arbitration Decisions - Escudero, Laura Martín (HERMES - Journal of Language and Communication in Business, 2011)
Over the last decades, linguists have drawn special considerations to deﬁne specialized discourse. Basically, the complexity of describing specialized discourse lies in its multi-dimensional nature. The main purpose of this paper is to characterize specialized discourse in WIPO Domain Name Arbitration as the result of social and institutional conditionings. First, the study focuses on characterizing text-external factors associated with this highly-specialized professional practice. More in particular, the study focuses on the analysis of ‘Quality’ in WIPO Domain Name Arbitration decisions. Second, the study found useful to deﬁne the boundaries of ‘specialized discourse’ Third, the study limited the focus of attention on analyzing ‘Quality’ in relation to ‘Objectivity’ and ‘Neutrality’ as factors associated with specialized discourse and also to ‘Impartiality’ and ‘Independence’ as conditionings speciﬁcally related to WIPO domain name arbitration professional practice. Following Bhatia (Bhatia 2004) this study conceptualizes specialized discourse as a concept highly dependent on social and institutional conditions.